112k views
2 votes
Solve the system of equations.- 2x + y=-43x – 2y = 1

1 Answer

1 vote

To solve the system of equations:


\begin{gathered} -2x+y=-4 \\ 3x-2y=1 \end{gathered}

We solve the first equation for y:


\begin{gathered} -2x+y=-4 \\ y=2x-4 \end{gathered}

And plug the value in the second equation


\begin{gathered} 3x-2(2x-4)=1 \\ 3x-4x+8=1 \\ -x=1-8 \\ -x=-7 \\ x=7 \end{gathered}

Once we have the value of x, we plug this value in the equation of y:


y=2(7)-4=14-4=10

Therefore, x=7 and y=10.

User Ernst Zwingli
by
4.3k points